25.0k views
0 votes
Graph y=(x+4)(-x+64)
Y=-x^2+68

1 Answer

0 votes

Answer:

Find the attached

Explanation:

We have been given the following functions and required to graph them;

y=(x+4)(-x+64)

Y=-x^2+68

We can expand the expression in the first equation;

(x+4)(-x+64) = -x^2+64x-4x+256 = -x^2+60x+256

The first equation can thus be written as;

y = -x^2+60x+256

We can now proceed to employ graphing utilities such as desmos graphing to plot these two equations on the same graph;

y = -x^2+60x+256

Y=-x^2+68

Find the attached;

Graph y=(x+4)(-x+64) Y=-x^2+68-example-1
User Tom Yates
by
5.3k points